Weekend warriors, physical activity pattern and all-cause mortality: a prospective study of 150,145 Mexican adults with and without hypertension - De Moraes-Ferrari, G (BMC, 2025)
Background Hypertension is associated with higher risk of premature all-cause mortality. Regular physical activity has been associated with reduced risk of all-cause mortality. In this study, we aimed to examine the association between physical activity patterns and all-cause mortality in adults with and without hypertension. Methods We included 150,145 participants (31,228 with hypertension) from the Mexico City Prospective Study. Cox regression model was performed to estimate the associations of frequency (no sport or exercise, weekend warrior, and regularly active) and duration (<30; or >= 30 min/day of sport or exercise) of physical activity with all-cause mortality in adults with and without hypertension. Results Over 15.6 years of follow-up, 25,295 deaths occurred, with 8,957 among adults with hypertension. Compared to those engaging in no sport or exercise, both weekend warriors (HR: 0.65, 95% CI 0.48-0.87 for adults without hypertension; HR: 0.70, 95% CI 0.50-0.91 for adults with hypertension) and those regularly active (HR: 0.79, 95% CI 0.59-0.99 for adults without hypertension; HR: 0.85, 95% CI 0.73-0.97 for adults with hypertension) had lower all-cause mortality. Engaging in sport or exercise sessions lasting >= 30 min/day showed a stronger associationwith lower all-cause mortality both in adults with and without hypertension. Both weekend warrior and regularly active individuals exhibited lower all-cause mortality risk estimates among those without hypertension compared with those with hypertension. Conclusions Weekend warriors and regularly active physical activity patterns were associated with lower all-cause mortality in adults without and with hypertension, particularly when session duration was >= 30 min/day.